The vulnerability of water availability in Peru due to climate change: A probabilistic Budyko analysis - Huerta, Adrian (2020)
This study provides for the-first-time a water availability analysis at drainage and basin-scale in Peru. Using new gridded datasets of precipitation and temperature, along with six global actual evapotranspiration estimations from remote sensing products, the vulnerability of water resources due to climate change is evaluated. This is addressed under a bottom-up approach and probabilistic Budyko framework that enables us to measure the associated uncertainty. First, to select an adequate estimation of long-term actual evapotranspiration, we compared at basin-scale the remote sensing products with long-term actual evapotranspiration inferred from a waterbalance (precipitation minus discharge) and deterministic Budyko (aridity and evaporative index relationship). Later, the probabilistic Budyko is calibrated using the adequated remote-sensed actual evapotranspiration and is cross-validated at country, drainage, and basin-scale.